MathsGee Answers is Zero-Rated (You do not need data to access) on: Telkom | Dimension Data | Rain | MWEB
First time here? Checkout the FAQs!
x

ASK - ANSWER - COMMENT - VOTE - DONATE


Network: Global | Joburg Libraries | MOOCs | StartUpTribe | Zimbabwe | Donate

MathsGee is Zero-Rated (You do not need data to access) on: Telkom |Dimension Data | Rain | MWEB

0 like 0 dislike
23 views

Determine the value of f'(x) from the first principle if f(x)=2x2-3x-5

in Mathematics by Wooden (162 points) | 23 views

1 Answer

0 like 0 dislike

From the first principle, we know that,  \(f'(x) = \lim\limits_{h \to 0} \frac{f(x+h)-f(x)}{h}\), now what we have to do is to plugin \(f(x+h)\) and \(f(x)\), simplify and find the limit.

\(f'(x) = \lim\limits_{h \to 0} \frac{f(x+h)-f(x)}{h} \\ f'(x) = \lim\limits_{h \to 0} \frac{ 2(x+h)^2 -3(x+h)-5-2x^2 +3x+5}{h} \\ f'(x) =\lim\limits_{h \to 0} \frac{2x^2 +4xh +2h^2-3x-3h-5-2x^2+3x+5}{h}\\ f'(x) = \lim\limits_{h \to 0} \frac{4xh+2h^2-3h}{h} \\ f'(x) = \lim\limits_{h \to 0} \frac{h(4x+2h-3)}{h} \\ f'(x) = \lim\limits_{h \to 0} 4x +2h -3\\ f'(x) = 4x-3 \)

Hence the final answer is \(f'(x) = 4x-3\)

by Wooden (882 points)

MathsGee Answers is a global, STEM-focused Q&A platform where you can ask people from all over the world educational questions for improved outcomes.



On MathsGee Answers, you can:


1. Ask questions
2. Answer questions
3. Comment on Answers
4. Vote on Questions and Answers
5. Donate to your favourite users

MathsGee Tools

Math Worksheet Generator

Math Algebra Solver

Trigonometry Simulations

Vectors Simulations

Matrix Arithmetic Simulations

Matrix Transformations Simulations

Quadratic Equations Simulations

Probability & Statistics Simulations

PHET Simulations

Visual Statistics

Interactive Courseware

ZeroEd Search Engine

Article Rewriter Tool

Word Counter Tool

Other Tools

STEM Gender Equality | ZOOM | Slack | eBook